Sagot :
Answer:
-3
Step-by-step explanation:
6(y-4)+(y+1)²
y=2
then,
6(2 - 4) + (2+1)²
6(-2) + (3)²
-12 + 9
-3
[tex]\red{⊱┈───────────────────────┈⊰}[/tex]
Evaluate the algebraic expression 6(y-4)+(y+1)² when y=2.
SOLUTION :
[tex]\rm \: putting \:\: y = 2 \: \: in \: \: 6(y - 4) + (y + 1) {}^{2} \\ \rm \: we \: set \: , \: 6(2 - 4) + (2 + 1) {}^{2} \\ \rm = 6( - 2) + 3 {}^{2} \\ \rm = - 12 + 9 \\ \rm = \: - 3[/tex]
ANSWER :
- -3
=======================================
[tex]\red{⊱┈───────────────────────┈⊰}[/tex]
#CarryOnLearning
(ノ^_^)ノ